Desnaturalizando los fines del intercambio comercial: los límites del lucro y la usura en Tomás de Aquino (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
The purpose of this text is to show how Aquinas understands economic activity based on the need that subjects have to exchange goods and solve the shortcomings of life and, at the same time, establishes a clear distinction between the desire for profit and the satisfaction of needs. This means that for Aquinas the desire for enrichment and profit is not part of human nature, since it must be directed to the supreme good and not to the satisfaction of needs through the market.
Keywords: Aquinas; Usury; Profit; Market; End